All-to-all trading in the U.S. treasury market - Alain Chaboud; Ellen Correia Golay; Caren Cox; Michael J. Fleming; Yesol Huh; Frank Keane; Kyle Lee; Krista Schwarz; Clara Vega; Carolyn Windover (Federal Reserve Bank of New York, 2022)
While the U.S. Treasury market remains the deepest and most liquid securities market in the world, several episodes of abrupt deterioration in market functioning over recent years have brought the market's resilience into focus. The adoption of all-to-all trading in the Treasury market could be one avenue to strengthen market resilience. Conceptually, all-to-all trading would allow any market participant to trade directly with any other market participant. This could be particularly helpful in times of stress, when the capacity of traditional intermediaries may be tested. In this paper, we discuss what all-to-all trading would mean for the cash secondary Treasury market, the benefits it might bring, and the conditions that might make adoption of the protocol more likely. We also review several trading protocols operating in the Treasury market that widen the field of trading partners and discuss the challenges to broader adoption of such protocols.
Keywords: G10; G23; D47; 330; Treasury market; market structure; all-to-all